Perception of Faculty Members as Role of Medical Facilitator in Private Sector Medical College - Qasim Saleem, Fatima Aslam, Muhammad Usman, Farrukh Sarfraz, Noor-Ul-Ain, Fahad Sarfraz, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Teachers are supposed to give students really good education that helps them get ready for the tough situations they may face in their medical careers. Teachers should know and be good at what they are teaching, and they should use ways that help students to learn and understand what they are being taught. Teachers are supposed to help and guide students, especially when they are learning how to take care of patients. They should be ready to help students who are having a hard time with school or any personal issues. Objective: To understand the perception of faculty members as role of medical facilitator in Private sector medical college Study design: Quantitative cross sectional Settings: Bakhtawar Ameen medical college Duration: Four months i.e. 1st August 2022 to 31st December 2022 Data Collection procedure: A pre validated questionnaire was used. Study was carried out at Bakhtawar Ameen Medical & Dental College, Multan. The total numbers of faculty members were 30 who participated after taking the informed consent. The study was done by simple random sampling technique. 12 items questionnaire were used. Google link form was used to collect the data. Results: There were 30 participants who were responded through google online link form. The twelve roles further subdivided into six dimensions. In this study there were 18 males and 12 females. All percentages regarding each attribute for twelve roles of medical teacher were very high. This study highlighted the various six dimensions in which all twelve roles of medical teachers grouped. This study highlighted most important role as facilitator 94% and least 89% as assessor. Conclusion: The success of any educational program hinges on the presence of an effective teacher. There is a shift in the teacher's role within the educational process. It is essential for teachers to evaluate their own performance in order to evolve from being mediocre to good, good to exceptional, and exceptional to the very best. Keywords: perception, medical teacher, facilitator, students, college